The Holy Spirit as the Power of Diversity: A Pneumatology of Religious Pluralism - Phan, Peter C. (Archīum Ateneo, 2022)
In celebration of the quincentennial of the arrival of Christianity in the Philippines, this essay discusses how religious diversity and pluralism can be reconciled with the Christian belief in Jesus as the Savior. I begin by examining the diverse ways in which the Holy Spirit works in the world according to the Hebrew Scripture, the Synoptic Gospels, Acts 2: 1-13, and Paul and by drawing on the document The Holy Spirit at Work in Asia of the Federation of Asian Bishops’ Conferences. Next, the essay examines how Jesus and the Spirit function autonomously, albeit not independently, from each other by making use of Saint Irenaeus’s teaching on the Two Hands of God. The last part of the essay examines the teaching of Pope Francis on how Christian mission is to be carried out while acknowledging the presence and work of the Spirit in other religions.